(untitled) (Economic and Political Thought, 2015)
The article discusses a new vision of European integration formulated by Guy Verhofstadt, a charismatic and uncompromising leader of European liberals. The vision is based on six points that require re-evaluation: new federalism and democratization of the Union, a reform of the European finances, environmental policy, European alter-globalism, the European Union security policy and the military of the European Union, and foreign policy. Liberals, despite political difficulties and a failure in the last European elections are still a major force in the European Parliament. ALDE is able to create a fresh concept of integration tailored to the dynamic changes on the continent.